CIRCUMCISION TRENDS IN PAKISTAN - Khalid Mahmood; Zahid Mahmood Nagra; Shahbaz Ahmad; Akram Malik (Journal of University Medical & Dental College, 2015)
ABSTRACT: BACKGROUND: Circumcision is the most widely performed surgical procedure in Muslim countries like Pakistan. It is performed by a variety of health care providers and different surgical procedures are employed. OBJECTIVES: The aim of the study was to analyze the trends of circumcision by medical specialty including the types of surgical techniques, usage of analgesia, complications and post-operative care employed by the various practitioners. STUDY DESIGN: Cross-sectional survey METHODS: A questionnaire asking about practices in the circumcision of neonates was sent to 150 health care providers including urologists, general surgeons, plastic surgeons, pediatrics surgeons, pediatricians, gynecologists and general practitioners in major cities of Pakistan. We received 90 replies. Details regarding the preferred techniques, type of analgesia, post operative care and complications were enquired about. The results were tabulated and analyzed. RESULTS: A total of 90 questionnaires were received from health care providers. The popular surgical technique for circumcision is with bone cutter which is used mainly by GPs and general surgeons. Plastic surgeons and urologist prefer the open dissection method. Most of the pediatrics surgeons apply the plastibell device. Pediatricians & gynecologists used the Gombo clamp. Most people used no analgesia. Pediatric surgeons and urologist used dorsal nerve block with paracetamol suppositories. Commonest complication noted was bleeding followed by superficial infection. Injuries to the glans or urethra were rare but serious complications. CONCLUSION: Circumcision with plastibell is the procedure of choice with a low rate of complications. This is used by most of the pediatrics surgeons. Bone cutter procedure is used by general surgeons and general practitioners .Bleeding is most common complication among all.